The synthesis and application of the Fe3O4@SiO2 nanoparticles functionalized with 3-aminopropyltriethoxysilane as an efficient sorbent for the adsorption of ethylparaben from wastewater: Synthesis, kinetic, thermodynamic and equilibrium studies. Issue 5 (October 2019) - Sheikhmohammadi, Amir; Safari, Mahdi; Alinejad, Abdolazim; Esrafili, Ali; Nourmoradi, Heshmatollah; Asgari, Esrafil
Abstract: The current study aimed at employing Fe3 O4 @SiO2 nanoparticles functionalized with NH2 (FSN) to remove Ethylparaben (EtP) from aqueous solutions. A modified co-precipitation method was applied to prepare the nanoadsorbent. The FTIR, XRD, SEM, VSM, and BET techniques were used to determine the structure, particle size, magnetic properties and specific surface area of adsorbent. The performance of FSN in the adsorption of EtP was investigated and removal performance obtained 93% under the selected conditions (pH, 7; adsorbent dosage, 0.4 g L −1 ; EtP concentration, 50 mg L −1 ; and reaction time, 90 min). It was found that FSN nanoadsorbent can be used for five cycles with no significant activity loss in the removal of ethylparaben. In order to determine of the adsorption capacity of the adsorbent and to investigate the mechanisms of adsorption, equilibrium data were fitted onto the Freundlich, Temkin, and Langmuir isotherms. The results was showed, the Freundlich isotherm model has the best fit with the experimental data. Furthermore, the kinetic models including pseudo-first-order, pseudo-second-order, intraparticle diffusion and elovich were applied to investigate the reaction pathways and determination of mechanism of sorption reaction. As reported results the best kinetic model was the pseudo-second-order model. Also the thermodynamic studies declared the sorption of EtP onto FSN was endothermic and spontaneous.